Creatine and the plurality of its uses, with emphasis on its supplementation in sports - Mikołaj Minkner; Piotr Petryla; Kamil Ostafin; Krzysztof Edyko; Zuzanna Suwała; Krzysztof Feja; Borys Bieńkowski; Urszula Marchewka; Ewa Łuczak; Natalia Rektor (Kazimierz Wielki University, 2023)
Introduction: Creatine is a non-protein amino acid that is synthesized endogenously mainly in the liver, kidney or pancreas, and also supplied exogenously with food, especially meat. The use of dietary supplements containing creatine is becoming increasingly popular, as evidenced by sales of $400 million per year. Aim of the study: The aim of our study was to evaluate the potential applications of exogenous creatine with a particular focus on its use in sport. State of Knowledge: Regular use of creatine contributes to water retention in the body as well as muscle hypertrophy. This leads to improved athletic performance, faster recovery as well as a shorter recovery period after injury. The potential use of creatine as an aid in the treatment of depression seems extremely interesting, but these reports require further research. Conclusion: Creatine is currently one of the most popular dietary supplements. Not only is it widely used in sport, where it shows a number of benefits, but research is also underway into its use in medicine.